Prophylactic role of Timolol to prevent rise of intraocular pressure after Nd-YAG laser posterior capsulotomy (Nepal Medical College Journal, 2023)
This study was conducted to know the effectiveness of topical 0.5% timolol maleate for the intraocular pressure rise after Nd-YAG laser posterior capsulotomy. Ninety-six eyes of 92 patients undergoing Nd-YAG laser posterior capsulotomy were randomly selected for pretreatment with topical 0.5% timolol maleate, 48 patients (Group A) or control 48 patients (Group B). The mean IOP of the group A was 14.8±3.0 mmHg before capsulotomy and 15.7±3.4 mmHg after capsulotomy (P >0.05), whereas 15.1±3.3 mmHg and 17.2±4.3 mmHg (P 0.05), but statistically significant difference between two groups after capsulotomy (P